Case reportGestation in patients with high levels of anticardiolipin antibodies, a history of deep venous thrombosis and miscarriages - de Godoy, José Maria Pereira; Spegiorin, Ligia Cosentino Junqueira Franco; Dallaqua, Juliana; de Carvalho, Cecília Freire de Carvalho; Costa, Iara Lima (Archives of Medical Science, 2006)
The aim is to stress the importance of prophylaxis against deep venous thrombosis in gravidas with high levels of anticardiolipin antibodies with or without a history of repetitive miscarriages. The evolutions of two gravidas who were treated in pre-natal and vascular surgery outpatients’ clinics and who suffered from deep venous thrombosis, miscarriages and high anticardiolipin antibody levels are reported. The gestations terminated at full term after prophylaxis for miscarriages was applied. The report suggests that patients with deep venous thrombosis and high anticardiolipin antibody levels may present with miscarriages and, therefore, prophylactic treatment is recommended.